CFD Simulation Study on Shell Made of Composite Material when Subject to Temperatures Above 3000 Degrees Centigrade - Hari Venkateswara Rao, C.; Usha Sri, P.; Ramanarayanan, R. (Journal of New Developments in Chemistry, 2020)
In this article I am explaining the Computational Fluid Dynamics (CFD) simulation study on shell made of Composite material when subject to Temperatures above 3000ºC. In this analysis a shell is made of the composite structure with all the properties defines as of the Carbon Phenolic materials and is subjected to temperatures of 3000ºC and the flow pattern over the surface is studied and the velocity gradients on the shell when travelling with such high speeds and temperatures are studied. This simulation study can be used to predict the flow simulation in various applications of heat transmission. This CFD simulation study results are useful to make a CP composite material for better thermal applications in aerospace industry.
Keywords: CFD; CP shell; transient.